Reflections on applying critical discourse analysis methodologies in analysing South African history textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article is a reflection on the choice to apply Critical Discourse Analysis (CDA) in a large scale study in which South African history textbooks were analysed for their construction of African consciousness. The article begins with an evaluation of history textbooks analysis as a field of study. It then explains my rationale for adopting CDA in a field where most studies are qualitative content analyses. This is followed by the explanation of my practical adaptation and application of Norman Fairclough’s version of CDA mixed with functional linguistics and visual semiotics. Only a few examples of the findings in the larger scale study are given to elaborate on this application. The article ends with a reflective evaluation of my application of CDA. I conclude that, though fraught with challenges, the application of CDA offers a worthwhile alternative methodology in the analysis of history textbooks.
Keywords: Critical Discourse Analysis (CDA); History textbooks; Methodologies; Africa; Africanness; South Africa